2019
DOI: 10.1021/acs.nanolett.9b01260
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Nanolasers Enhanced by Hybrid Graphene–Insulator–Metal Structures

Abstract: Graphene is a two-dimensional (2D) structure that creates a linear relationship between energy and momentum that not only forms massless Dirac fermions with extremely high group velocity but also exhibits a broadband transmission from 300 to 2500 nm that can be applied to many optoelectronic applications, such as solar cells, light-emitting devices, touchscreens, ultrafast photodetectors, and lasers. Although the plasmonic resonance of graphene occurs in the terahertz band, graphene can be combined with a nobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 47 publications
(81 reference statements)
2
40
0
2
Order By: Relevance
“…Furthermore, due to surface defects and low carrier injection efficiency, nano/microstructures exhibit broadband emissions and inherently low external efficiency, which severely reduce their ability to meet scientic and commercial demands. [14][15][16] When coupled with light at specic photon energies, collective oscillations of conduction electrons in metallic nanostructures can be excited. The spectral properties of these excitations, called plasmons, have attracted widespread scientic and technological interest.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to surface defects and low carrier injection efficiency, nano/microstructures exhibit broadband emissions and inherently low external efficiency, which severely reduce their ability to meet scientic and commercial demands. [14][15][16] When coupled with light at specic photon energies, collective oscillations of conduction electrons in metallic nanostructures can be excited. The spectral properties of these excitations, called plasmons, have attracted widespread scientic and technological interest.…”
Section: Introductionmentioning
confidence: 99%
“…[ 34–36 ] We propose the design of a graphene–insulator–metal (GIM) platform, as shown in Figure a, and demonstrated that its SPP propagation properties are influenced by graphene. [ 37 ] In the configuration of the GIM platform, when the current is applied to graphene, the plasmon phase velocity can approach the Fermi velocity ( v f = c /300, where c is the speed of light in a vacuum) of the graphene by tuning the insulator thickness in the GIM platform; [ 38 ] therefore, it is possible to generate nonreciprocal SPP waves to realize novel nanophotonic devices. [ 39,40 ]…”
Section: Figurementioning
confidence: 99%
“…ZnO/石墨烯/绝缘层/金属层(GIM)的结构, 可以修正 S P P 色 散 特 性 并 消 除 金 属 固 定 等 离 子 体 特 性 的 限 制 [106] . 由于费米能级的差异, 石墨烯的加入会改变金 [101] .…”
Section: 示 为了追求更低阈值的纳米激光器 他们又构建了unclassified
“…(b) 亚波长金属Ag光栅与ZnO纳米棒结合的纳米激光器受激辐射谱, 插图为该激光模式电 场分布图 [103] ; Copyright © 2015 American Chemical Society. (c) GIM结构ZnO纳米激光器的原理示意图, 插图为Al基GIM结构的电场分布图; (d) 四种结构的纳米激光器平均阈值图 [106] . Copyright © 2019 American Chemical Society Figure 10 (Color online) SPP coupled ZnO nanolaser.…”
Section: 示 为了追求更低阈值的纳米激光器 他们又构建了unclassified
See 1 more Smart Citation